The density of endometrial glandular openings: a novel variable to predict the live birth rate in patients with intrauterine adhesions following hysteroscopic adhesiolysis. Issue 4 (22nd January 2021) - Zhao, Xingping; Gao, Bingsi; Yang, Xuan; Zhang, Aiqian; Jamail, Grace; Li, Yueran; Xu, Dabao
Abstract: STUDY QUESTION: Can the density of endometrial glandular openings (DEGO) be a reliable and simple new variable in the prediction of live birth after hysteroscopic adhesiolysis? SUMMARY ANSWER: The DEGO grade at follow-up hysteroscopy outperforms American Fertility Society (AFS) score in predicting the live birth rate after hysteroscopic adhesiolysis for patients with intrauterine adhesions (IUAs). WHAT IS KNOWN ALREADY: Several methods, such as endometrial thickness and AFS score, have been proposed for predicting the live birth rate in patients with IUAs who undergo hysteroscopic adhesiolysis. STUDY DESIGN, SIZE, DURATION: A test cohort of 457 patients with IUAs who underwent hysteroscopic adhesiolysis and had satisfactory follow-up hysteroscopy videos were retrospectively enrolled between January 2016 and January 2017. A validation cohort comprising 285 IUA patients was prospectively enrolled from March 2018 to August 2018. PARTICIPANTS/MATERIALS, SETTING, METHODS: An automated counting software tested the follow-up hysteroscopy videos to calculate the DEGO grade of all the 742 patients with IUAs after hysteroscopic adhesiolysis. The AFS score for each patient was also calculated at the same follow-up hysteroscopy. Logistic regression analysis was performed to develop prediction models to predict the live birth rate following hysteroscopic adhesiolysis. The performance of each of these prediction models was compared by calculating the AUC. MAIN RESULTS AND THE ROLE OF CHANCE: In the test cohort (n = 457), 231 patients had a live birth, but 226 patients failed. In the validation cohort (n = 285), 117 patients had a live birth, while 168 patients did not. The logistic regression analysis revealed that both the DEGO grade and AFS score at follow-up hysteroscopy were closely correlated with the live birth rate in patients with IUAs ( P  = 0). The AUCs of AFS score and DEGO grade in the test cohort were 0.7112 and 0.8498, respectively ( P  < 0.0001). The AUCs of AFS score and DEGO grade in the prospective external validation cohort were 0.6937 and 0.8248, respectively ( P  < 0.0001). LIMITATIONS, REASONS FOR CAUTION: Further well-designed prospective clinical studies with a multicentric larger sample size should be needed to confirm the feasibility and efficacy of DEGO. WIDER IMPLICATIONS OF THE FINDINGS: The DEGO grade is an accurate predictor factor of live birth rate in patients with IUAs following hysteroscopic adhesiolysis and can represent in the future an important and promising tool for assessing obstetric outcomes in IUAs. STUDY FUNDING/COMPETING INTEREST(S): This study is supported by National Key Research and Development Program of China (Grant No. 2018YFC1004800), Natural Science Foundation of China (Grant No. 81671492), Natural Science Foundation of Hunan (Grant No. 2020JJ5859). B.G. is supported by Chinese Scholarship Council (File number. 201806370178). The authors have no conflicts of interest to declare. TRIAL REGISTRATION NUMBER: N/A